Sturts Stony Desert, Central Australia - Twidale, Rowl; Bourne, Jennifer (ERDKUNDE, 2002)
Ignorant of the existence of a similar geographical feature in any other part world, I was at a loss to divine its nature (Sturt 1849, 373, on the stony desert that now bears his name). Sturts Stony Desert is part of the Simpson Desert of central Australia, and as its name suggests is dominated by hamada or gibber. The gibber consists of angular fragments of silcrete derived from the dissection and disintegration of a siliceous duricrust developed on later Mesozoic strata during the Oligocene and Miocene. The faceted slopes bordering the valleys of incised streams have been worn back leaving behind a surface of low relief, largely of etch type, and carrying lag deposit of silcrete stones which forms a protective veneer. Nevertheless, where the gibber crust has been breached gullying is common.